Computed Tomography–Colonography With Intravenous Contrast Medium and Urographic Phase for the Evaluation of Pelvic Deep Infiltrating Endometriosis of Intestinal and Urinary Tract. Issue 3 (May 2019) - Coppola, Francesca; Paradisi, Roberto; Zanardi, Sara; Papadopoulos, Dimitris; Gramenzi, Annagiulia; Valerio, Domenico; Pierotti, Luisa; Zannoni, Letizia; Seracchioli, Renato; Golfieri, Rita
Abstract : Objectives: The aim of this study was to evaluate the diagnostic accuracy of a specific protocol of computed tomography–colonography with intravenous contrast medium and urographic phase, which combined simultaneously the study of the intestinal and urinary tract, in the preoperative evaluation of women with deep infiltrating endometriosis (DIE) of anterior and posterior pelvic compartments. Methods: We retrospectively analyzed 73 women who underwent 74 computed tomography–colonography with intravenous contrast medium and urographic phase examinations for strong clinical suspicion of DIE. All the women had surgical confirmation. Results: Computed tomography–colonography with intravenous contrast medium and urographic phase in detecting DIE rectosigmoid involvement had a sensitivity of 82.3% and a specificity of 66.7%, while in detecting DIE urinary tract involvement had a sensitivity of 45.9% and a specificity of 78.4%. Conclusions: Computed tomography–colonography with intravenous contrast medium and urographic phase is a useful technique for the preoperative planning of selected women with DIE, in particular, for the detection of sigmoid colon and bladder lesions especially when performed with a dose reduction protocol.